The Current State of Support for Ikigai Shugyo at Daycare Facilities with a focus on Specific Support Methods - SAGAWA, Kanae; KAWASAKI, Ippei; MORIMOTO, Seiji; HARADA, Shun; OGAWA, Noriyuki; OGAWA, Yoshinori; NAGAI, Kuniaki (The Journal of Science of Labour, 2022)
‘Ikigai Shugyo’ is a system in Japan whereby the elderly engage in work for the purpose of finding ikigai (motivation). In this study, the current state of ikigai shugyo support being provided in daycare facilities was investigated using micro-ethnography. The results of the study revealed that the users and staff should promote an understanding of ikigai shugyo and create an environment where the service-users and volunteers can play an active role. Additionally, the results also revealed that when collaborating with entities external to the facilities, searches for potential partner companies can be made by utilizing a nearby regional network in addition to consultation, for innovation in product development derived through collaboration with stakeholders.